Antiviral supramolecular polymeric hydrogels by self-assembly of tenofovir-bearing peptide amphiphiles. (30th November 2022) - Monroe, Maya K.; Wang, Han; Anderson, Caleb F.; Qin, Meng; Thio, Chloe L.; Flexner, Charles; Cui, Honggang
Abstract : Tenofovir-conjugated peptide amphiphiles can assemble and form hydrogels under physiological conditions for sustained therapeutic release. Varying the number of valines in the designs impacts their self-assembly, gelation, and release behavior. Abstract : The development of long-acting antiviral therapeutic delivery systems is crucial to improve the current treatment and prevention of HIV and chronic HBV. We report here on the conjugation of tenofovir (TFV), an FDA approved nucleotide reverse transcriptase inhibitor (NRTI), to rationally designed peptide amphiphiles (PAs), to construct antiviral prodrug hydrogelators (TFV-PAs). The resultant conjugates can self-assemble into one-dimensional nanostructures in aqueous environments and consequently undergo rapid gelation upon injection into 1× PBS solution to create a drug depot. The TFV-PA designs containing two or three valines could attain instantaneous gelation, with one displaying sustained release for more than 28 days in vitro . Our studies suggest that minor changes in peptide design can result in differences in supramolecular morphology and structural stability, which impacted in vitro gelation and release. We envision the use of this system as an important delivery platform for the sustained, linear release of TFV at rates that can be precisely tuned to attain therapeutically relevant TFV plasma concentrations.